2011
DOI: 10.1111/j.2042-7166.2011.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of herbal medicine use among surgical patients in Trinidad

Abstract: The aim of this study is to determine the prevalence of herbal medicine usage among surgical patients in three hospitals in Trinidad. The study population comprised 303 surgical outpatients randomly selected from the three hospitals. All patients were over 18 years of age. Eligible participants either had surgery within the previous year or were due for surgery within the following 6 months. Of the 303 subjects, 121 (40%) reported the use of herbal medicines. Twenty‐five percent of patients attending Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Studies carried out in Jamaica and Trinidad have found interesting results concerning the relationship between education and the use of botanical medicines. In these studies, the respective prevalence of medicinal plant use among participants was inversely proportional to level of education attained; use was consistently lowest among participants with tertiary education (i.e., post-secondary), and the highest among participants with little to no education (Mahabir and Gulliford, 1997;Merritt-Charles, 2011;Picking et al, 2011). One study investigated the factors affecting the decision to use botanical medicines among asthmatic patients in Trinidad; interestingly, Garlic (Allium sativum L.) and Echinacea (Echinacea purpurea (L.) Moench) were the preferred plant species among users with higher levels of educationboth of which have strong scientific evidence supporting their medicinal properties (Clement et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies carried out in Jamaica and Trinidad have found interesting results concerning the relationship between education and the use of botanical medicines. In these studies, the respective prevalence of medicinal plant use among participants was inversely proportional to level of education attained; use was consistently lowest among participants with tertiary education (i.e., post-secondary), and the highest among participants with little to no education (Mahabir and Gulliford, 1997;Merritt-Charles, 2011;Picking et al, 2011). One study investigated the factors affecting the decision to use botanical medicines among asthmatic patients in Trinidad; interestingly, Garlic (Allium sativum L.) and Echinacea (Echinacea purpurea (L.) Moench) were the preferred plant species among users with higher levels of educationboth of which have strong scientific evidence supporting their medicinal properties (Clement et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Unlike its neighboring islands, Barbados was colonized primarily by the British and did not have the influx of indentured servants observed in other southern Caribbean islands ( Lane, 1979 ). While a wealth of literature exists on traditional botanical medicine in larger Caribbean countries ( Mahabir and Gulliford, 1997 ; Merritt-Charles, 2011 ; Clement et al, 2005 ), there is a need for more comprehensive studies to be done on this topic in smaller islands such as Barbados, as they were subject to a stronger degree of cultural suppression ( Abrahams, 1967 ). For instance, smaller islands typically had smaller plantations, which meant fewer slaves and greater oversight from the plantation owners, as well as a greater adoption by slaves of the attitudes and expressions of the owners ( Abrahams, 1967 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of use of herbal medicinal products (HMPs) is high and continues to increase. This applies to the UK [1] as well as other parts of the world [2]. It is therefore important to be aware of the safety issues associated with the administration of HMPs [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite chiropraxis is visible represented in all European countries, less frequently reported use of this treatment in Slovakia could be explained by absence of possibilities to solve different musculoskeletal problems by experts trained in chiropraxis. The increasing demand for herbal teas and related products has been confirmed in Western Europe (Hritcu & Cioanca, 2016; Wemrell et al, 2017) and other parts of the world (Merritt-Charles, 2011). However, unlike Western Europe, where we can see the re-emergence of alternative healthcare together with a strong medical counterculture since at least the mid-1960s, the situation in the Eastern European region has been quite different.…”
Section: Discussionmentioning
confidence: 99%